2015
DOI: 10.3748/wjg.v21.i6.1915
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus and Epstein-Barr virus infection in inflammatory bowel disease: Need for mucosal viral load measurement

Abstract: Viral colitis appeared to contribute to mucosal lesions in refractory IBD, and its correct diagnosis and management require quantitative real-time polymerase chain reaction assay of mucosal specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 53 publications
6
68
2
2
Order By: Relevance
“…Our study shows that 33.3% patients have EBV infection in colonic mucosa of IBD patients, lower than that reported by other researchers (45.5-81.0%) [7][8][9][10][11]15]. It may be due to the difference in patients enrolled.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Our study shows that 33.3% patients have EBV infection in colonic mucosa of IBD patients, lower than that reported by other researchers (45.5-81.0%) [7][8][9][10][11]15]. It may be due to the difference in patients enrolled.…”
Section: Discussioncontrasting
confidence: 75%
“…However, only a few studies have been found on this issue. To date, data about EBV positive rate in mucosa of IBD patients vary because of the difference in enrolled subjects, testing approaches, and study design [7][8][9][10][11]. EBV prevalence in colonic mucosa of Chinese IBD patients is not clear so far.…”
Section: Introductionmentioning
confidence: 99%
“…This high rate of CMV detection reflects the clinical sensitivity of CMV PCR in colonic tissue, and is in agreement with previous studies, demonstrating the high sensitivity and frequency of positive CMV PCR in steroid-refractory colitis [3,14,17,18]. In this regard, it has also been suggested that clinical outcomes correlate with the tissue viral load [19,20,21]. We thus expect that this rapid, sensitive and quantitative assay will be increasingly utilized in the diagnostic workup of patients with UC exacerbation, and further determination of its clinical significance is of high importance.…”
Section: Discussionsupporting
confidence: 90%
“…This patient's course, exemplifying the importance of PCR in diagnosis and therapeutic decisions, is comparable to that described in the case series by Roblin et al [21], which included 7 patients with a positive tissue CMV-PCR and negative IHC staining, who were treated successfully with antiviral therapy. We further found a positive correlation between the tissue CMV viral load and the tissue IHC staining that had not been observed in a previous report [20]. This difference could be attributed to differences in techniques and assay sensitivity.…”
Section: Discussionsupporting
confidence: 60%
“…Finally, it is known that steroid-refractory UC patients have a high incidence of human cytomegalovirus (CMV) [13][14][15][16]. It has also and underwent multiple wash-out surgeries.…”
Section: Case Reportmentioning
confidence: 99%